The Impact of Ethics Education on Earnings Management Judgment: A Quasi-Experimental Approach - Mahfud Sholihin, Mahfud Sholihin (2015)
This study examines the impact ofethics education on earnings management judgment using quasi-experiment approach involving MBA students in a major university in Indonesia as subjects. Particularly, we examine whether participants judge earnings management differently before and afte I' they do Business Ethics course. Additonally, we also compare those who take Business Ethics course and those who do not take it. Wefind no ethical judgment difference between students, before and after they do Business Ethics; and those who take and do not take Business Ethics course. Key words: Earnings Management, Ethics Education, Quasi-Experiment